Weed control in castor (Ricinus communis) - DUNGARWAL, H S; CHAPLOT, P C; NAGDA, B L (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during the rainy season of 1999 and 2000 to evaluate the relative efficacy of herbicides applied alone or in combinataion with supplemental hand-weeding 40 days after sowing to control weeds in castor (Ricinus communis L.) under irrigated ecosystem on sandy-loam soils. Pre-plant incorporation of fluchloralin (1.0kg/ha) effectivity controlled weed population and reduced weed density. However, theri effectiveness wsho greatly improved when these were applied in combination with 1 hoeing 40 days after sowing. Among the herbicides, pre-emergence application of alachlor @ 2.0 kg/ha supplemented with 1 hoeing at 40 days after sowing showed remarkable effect on reducing weed density (95%) and weed dry matter (89%) which ultimately led to higher seed yield (2.0 tonnes/ha) and fetching additional net returns of Rs 5 240/ha with benefit : cost ratio of 3.75.